The Iddah Period as an Instrument for Women's Protection: Criticism of Marriage in the Iddah Period (Study of the Director General of Islamic Guidance 2021) - Fahrul Hidayat, Muhammad; Ismail, Habib; Iwannudin, Iwannudin (STAINI Press, 2026)
This study aims to analyze the iddah period as an instrument of women’s protection and to critique the practice of remarriage conducted by a former husband while his ex-wife is still undergoing iddah, from the perspectives of fiqh, maqāṣid al-syarī‘ah, and Indonesian positive law. Essentially, the iddah period is a Sharia provision that functions as a multidimensional protection mechanism for women—safeguarding lineage, dignity, psychological well-being, and social stability after divorce. However, in practice, these protective values have not been fully realized, as cases of remarriage during iddah continue to occur due to limited public understanding and weak administrative supervision in the Office of Religious Affairs (KUA). This research employs a library-based normative approach, analyzing classical fiqh literature, maqāṣid al-syarī‘ah theory, the Compilation of Islamic Law (KHI), the Marriage Law, and the 2021 Circular Letter of the Director General of Islamic Guidance. The findings reveal a normative gap in Indonesian positive law, which does not explicitly prohibit men from remarrying while their former wives are still in iddah. Accordingly, this study recommends legal reform grounded in maqāṣid al-syarī‘ah to strengthen women’s protection through binding and effectively enforced regulations.